2011
DOI: 10.2478/s11534-010-0110-0
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of sensing mechanism of ethanol vapour in polymer-nanostructured carbon composite

Abstract: Abstract:Polymer-nanostructured carbon composites (PNCC) using three different polymers as composite matrix materials (polyvinylacetate (PVAc), polyethylene glycol (PEG) and ethylene-vinylacetate copolymer (EVA)) have been developed. High structure carbon black Printex XE2 (Degussa AG) was used as a composites filler. Ethanol vapour sensor-effect of composites was determined as a change of electrical resistance as the composite was held in ethanol vapour for 30 seconds. Reversibility of electrical resistance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It may involve swelling of the polymers caused by absorption of the analyte molecules causing changes in the extrinsic conductivity, and/or changes in the intrinsic conductivity due to charge-transfer interactions between the analytes and the polymers (Slater, Watt, Freeman, May, & Weir, 1992). The molecule approximate diameters of water, methanol and ethanol are 2.75, 3.90 and 4.71 Å, respectively (Sakale et al, 2011). Possibly, ethanol molecules are too big to fit in the free volume cavities of the polymer matrix, while water molecules, although smaller, are too lipophobic.…”
Section: Resultsmentioning
confidence: 99%
“…It may involve swelling of the polymers caused by absorption of the analyte molecules causing changes in the extrinsic conductivity, and/or changes in the intrinsic conductivity due to charge-transfer interactions between the analytes and the polymers (Slater, Watt, Freeman, May, & Weir, 1992). The molecule approximate diameters of water, methanol and ethanol are 2.75, 3.90 and 4.71 Å, respectively (Sakale et al, 2011). Possibly, ethanol molecules are too big to fit in the free volume cavities of the polymer matrix, while water molecules, although smaller, are too lipophobic.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The samples were dried at room temperature [ 20 ]. The schematic structure and the dimensions are illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous works [ 8 – 9 20 23 ], we determined that the EVA–CB sensing measurement increases when the layer thickness of EVA–CB is decreased or the vinyl acetate (VA) content in the copolymer is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Sakale et al [16,18] describes the procedure of sample making and sensor material geometrical design in detail. Previously, it has been found that Pi-NCC both sensitivity and response stability greatly influence the filler dispersion method used [16].…”
Section: Sample Preparationmentioning
confidence: 99%